2014
DOI: 10.1016/j.appet.2014.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Robust relation between temporal discounting rates and body mass

Abstract: Objective When given the choice between $100 today and $110 in one week, certain people are more likely to choose the immediate, yet smaller reward. The present study examined the relations between temporal discounting rate and body mass while accounting for important demographic variables, depressive symptoms, and behavioral inhibition and approach. Methods After having their heights and weights measured, 100 healthy adults completed the Monetary Choice Questionnaire, the Beck Depression Inventory-II, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
132
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 152 publications
(149 citation statements)
references
References 32 publications
12
132
3
1
Order By: Relevance
“…The current findings also have several important implications for our understanding of the behavioral economics of health decisions [29]. Prior studies have linked the behavioral economic concept of temporal discounting (time-based reward devaluation) to a range of poor health behaviors such as obesity [30], needle sharing in IV drug users [31], substance use and abuse [32], and risky sexual decision-making [33]. Yet, the connections between probability discounting and health behavior have been less clear even as important treatment decisions are made relying on subjective probabilistic comparisons of uncertain costs and benefits.…”
Section: Discussionmentioning
confidence: 88%
“…The current findings also have several important implications for our understanding of the behavioral economics of health decisions [29]. Prior studies have linked the behavioral economic concept of temporal discounting (time-based reward devaluation) to a range of poor health behaviors such as obesity [30], needle sharing in IV drug users [31], substance use and abuse [32], and risky sexual decision-making [33]. Yet, the connections between probability discounting and health behavior have been less clear even as important treatment decisions are made relying on subjective probabilistic comparisons of uncertain costs and benefits.…”
Section: Discussionmentioning
confidence: 88%
“…21,22,34,35,63 The CNDS hypothesis argues that a dysregulation in the relative balance between the executive and impulsive systems can predispose individuals to poor decision-making. 34,64 This poor decision-making has been intimately linked with maladaptive responses, such as drug abuse, 54,[65][66][67] gambling, 20,68 overeating/obesity, 19 and other poor health behavior. 18 By contrast, healthier individuals tend to show stronger relative activation in the executive system that subserves activities such as valuing future events, response inhibition, planning, working memory, and attention.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…17 Comparisons of patterns of neural activation during neurocognitive and cue-elicited tasks have isolated the brain regions associated with craving (eg, amygdala, ACC, dlPFC, OFC, and insula). Relatedly, executive functioning deficits in areas such as valuing future events (delay discounting), working memory, cognitive flexibility, risk taking, and attention are consistently related to substance abuse and other impulse control disorders (eg, obesity, gambling [18][19][20]. Analyses of the patterns of neural activation during these neurocognitive assessments suggest that task performance reflects the relative activation in two interconnected neurobiological systems: the evolutionarily older impulsive system, which is rewarddriven and housed in limbic and prelimbic areas (eg, ACC, amygdala), and the more recently evolved executive system, which underlies planning and self-control processes and is housed in prefrontal regions (eg, dlPFC).…”
Section: Cue-reactivity and Neurocognitive Task Paradigms: Findings Amentioning
confidence: 99%
See 1 more Smart Citation
“…Weller RE [20] reported that obese women had greater discounting of monetary rewards than healthy-weight women and that the discounting rates could not be explained by differences in earnings, age or IQ. Similarly, Jarmolowicz DP et al [21] found that delay discounting of monetary rewards was higher for obese and overweight participants than for healthy weight and underweight participants. A specific revision of studies that evaluate the discounting rate in people with different eating disorders can be found in McClelland et al [22].…”
Section: Introductionmentioning
confidence: 99%